Study of the potential of exogenous trehalose in preventing ascorbic acid degradation in heat-dried Lycopersicon esculentum fruit - Aguilar, Roel Joseph B.; Espiritu, Joan Camille P. (2012)
Ascorbic acid is a very good indicator of the quality of the food processing. This study aimed to show the effectiveness of exogenously applied trehalose in maintaining the ascorbic acid content in Lycopersicon esculentum fruit. Result of this study showed high concentrations of trehalose, especially trehalose powder, significantly reduced the degradation of ascorbic acid as the tomatoes were being heat-dried. The tomatoes applied with low concentration of exogenous trehalose showed no significant difference in the amount of their degraded ascorbic acid as compared to the untreated tomatoes. These may indicate the potentiality of exogenous in the prevention of ascorbic acid degradation in dried tomatoes if applied in higher concentration as a pre-treatment -- Author's abstract.